Evaluation of the antioxidant potential of some 5-(2-bromo-4-fluorophenyl)-4-ethyl-1,2,4-triazole-3-thiol derivatives - Kalchenko, V. V.; Shcherbyna, R. О.; Panasenko, O. I.; Salionov, V. О.; Morozova, L. P.; Кальченко, Валерій Володимирович; Щербина, Роман Олександрович; Панасенко, Олександр Іванович; Саліонов, Володимир Олександрович; Морозова, Л. П. (Дослідження антиоксидантного потенціалу деяких похідних 5-(2-бром-4-флуорофеніл)-4-етил-1,2,4-триазол-3-тіолу, 2024)
The purpose of the study. The present research explored the molecular docking and antioxidant activity of 5-(2-bromo-4-fluorophenyl)- 4-ethyl-1,2,4-triazole-3-thiol derivatives. These compounds were assessed for their potential as antiradical agents to counter oxidative stress caused by free radicals. Materials and methods. Molecular docking simulations were conducted to predict the interactions between the synthesized compounds and key amino acid residues of cytochrome c-peroxidase (PDB code: 2X08). The derivatives were prepared in docking-compatible formats to analyze binding energies. In vitro antiradical activity was evaluated using the DPPH assay, measuring the compounds’ ability to neutralize free radicals through color changes when DPPH loses its radical properties upon antioxidant interaction. Absorption was measured at 516 nm to quantify radical scavenging activity. Results and discussion. Molecular docking and in vitro testing showed most derivatives had antioxidant activity. The heptyl-containing compound displayed the highest antioxidant activity, marking it as a strong antiradical agent. Docking analysis confirmed strong interactions with the enzyme’s active sites, with compound 2e achieving the highest binding score, indicating its potential as an antioxidant. While some discrepancies emerged between DPPH assay results and molecular docking, the findings highlight these derivatives’ therapeutic potential against oxidative stress, linked to conditions like cardiovascular and neurodegenerative diseases, and cancer. Further research is recommended to optimize antioxidant efficacy and understand mechanisms of action, potentially leading to new antioxidant agents for medical and pharmaceutical applications against oxidative damage. Досліджено антиоксидантну активність восьми алкільних похідних 5-(2-бром-4-флуорофеніл)-4-етил-1,2,4-триазол-3-тіолу з використанням методу молекулярного докінгу та взаємодії з 2,2-дифеніл-1-пікрилгідразилом (DPPH). За результатами дослідження молекулярний докінг показав, що сполука 3-(2-бром-4-флуорофеніл)-4-етил-5-(пентилтіо)-4Н-1,2,4-триазол має більшу енергію взаємодії з ферментом цитохром с-пероксидазою (PDB код: 2X08) порівняно з іншими сполуками цього ряду. Водночас під час дослідження антиоксидантної активності методом DPPH встановлено, що сполука 3-(2-бром-4-флуорофеніл)-4-етил-5-(гептилтіо)- 4H-1,2,4-триазол продемонструвала найвищий рівень активності. Результати свідчать про потенціал цих сполук як антиоксидантів і обґрунтовують перспективи подальших досліджень.
Keywords: 1,2,4-triazole; antioxidant activity; molecular docking; DPPH; 1,2,4-триазол; антиоксидантна активність; молекулярний докінг